Physicians’ intentions to use digital tools – a comparative survey, before and after the COVID-19 pandemic, in Southern Sweden - Sofia Olofsson; Fredric Karlsson; Miriam Pikkemaat; Björn Ekman; Mattias Rööst; Hans Thulesius; Veronica Milos Nymberg (Scandinavian Journal of Primary Health Care)
Objectives To describe changes in Swedish primary care physicians’ use of, attitudes and intentions toward digital tools in patient care between 2019 and 2022.Design A survey using a validated questionnaire measuring physician’s intentions to use digital tools based on the theory of planned behavior.Setting Sample of primary health care centers in southern Sweden.Subjects Primary care physicians.Main outcome measures Self-reported use and intentions to use, digital tools including digital consultations by text or video, chronic disease monitoring and artificial intelligence (AI) and the associations between attitudes, subjective norms, perceived behavioral control and behavioral intentions to use digital tools, in 2019 compared to 2022.Results In both 2019 (n = 198) and 2022 (n = 93), physicians reported high intentions to use digital tools. Self-reported use of video was slightly higher in 2022 (p = .03). No other changes were seen in the self-reported use or behavioral intentions to use digital tools.Conclusion The slow adoption of patient-related digital tools in Swedish primary health care does not seem to be explained by a low intention to use them among physicians. Future research on implementation of digital tools should include a focus on contextual factors such as organizational, technical and cultural barriers.